2007
DOI: 10.1148/radiol.2422051994
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Pulmonary Valve Implantation Based on Rapid Prototyping of Right Ventricular Outflow Tract and Pulmonary Trunk from MR Data

Abstract: Using 3D RP models resulted in more accurate selection of patients for PPVI than did using MR images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
155
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(158 citation statements)
references
References 19 publications
2
155
0
1
Order By: Relevance
“…Minimal invasive procedures for the pulmonary valve are less traumatic, reducing valve replacement risk [3]. Percutaneous pulmonary valve implantation (PPVI) [4] is a new developed technique for transcatheter placement of a valve stent. The main difficulties of PPVI are: the assessment of the pulmonary trunk and the right ventricle outflow track (RVOT < 22mm) before treatment [4], the classification of patients suitable for the procedure [5] and identification of the exact location for anchoring the stent [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal invasive procedures for the pulmonary valve are less traumatic, reducing valve replacement risk [3]. Percutaneous pulmonary valve implantation (PPVI) [4] is a new developed technique for transcatheter placement of a valve stent. The main difficulties of PPVI are: the assessment of the pulmonary trunk and the right ventricle outflow track (RVOT < 22mm) before treatment [4], the classification of patients suitable for the procedure [5] and identification of the exact location for anchoring the stent [6].…”
Section: Introductionmentioning
confidence: 99%
“…The acquired data (4D CT) is usually translated into sets of 2D planes for manual quantification and visual evaluation due to the lack of appropriate methods and tools for processing 3D/4D information. Measurements are tedious to obtain and moreover known to be affected by inaccuracies, as 2D alignment and sectioning is ambiguous and might lead to misinterpretation and distensibility [4].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Similarly, good to excellent agreement has been reached between 3D printed models and original source 2D images for dimensional measurements of aortic valve, aortopulmonary artery, and aortic aneurysms. [21][22][23][24][25] However, in a recent study, Ho et al have indicated that the variances in aortic diameter measurements between 3D printed models and 2D contrastenhanced CT images exceeded 1.0 mm, which is beyond the standard deviation of 1.0 mm. 26 This highlights the potential limitations of using anatomic landmarks to measure accuracy of 3D printed hollow models, such as heart models or aneurysmal models.…”
mentioning
confidence: 99%
“…Previous studies have reported the accuracy of 3D printed models of cardiovascular disease with good to excellent correlation between 3D printed models and original CT or MRI data. [21][22][23][24][25] However, these studies are limited in assessment of diameter changes in the selected anatomical regions, which failed to consider the whole shapes of vascular structures or aneurysms. Further, according to a recent systematic review, majority of the current studies compared 3D printed models with original source CT or MRI data, 12,[21][22][23][24] while only a few of them compared images of the scanned 3D printed models with original source imaging data (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation